Decisions in Finance Management at Polish Financial Institutions - Credit Unions and the National Credit Union - Kędzierski, Leszek (Ekonomika, 2007)
Crediting financial institutions (financial co-operatives) on Polish territories began functioning in the 19th century. They performed duties also in the period of the 2nd Republic of Poland. After World War II, credit unions were subjected to various organizational transformations. Their regeneration in Poland took place early in the 1990s in the shape of the credit unions. The non-banking financial institutions in Poland - credit unions and the National Credit Union - take investment and financial decisions. These decisions deal with finance management. Investment decisions are not a uniform category. One can group them on various bases. The credit unions and the National Credit Union may take up various attitudes towards the investment risk. Financial decisions are determined by operational and investment activity of the mentioned financial institutions. The scope of investment and financial decisions of credit unions and the National Credit Union is different. There are external and internal factors, as well as mixed internal-external factors influencing at the present moment the investment and financial decisions of credit unions and the National Credit Union. Future changes within the investment and financial decisions of credit unions and the National Credit Union in Poland may be determined, among other factors, by the accepted model of development of these financial institutions (Model of QuantityQuality Changes - MQQC or Banking Model - BM).